2023
DOI: 10.1101/2023.08.16.23294155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population health impacts and associated monetary gains from the taxation of salt and sugar in the United Kingdom

Patricia Eustachio Colombo,
James Milner,
Silvia Pastorino
et al.

Abstract: Poor diets contribute to significantly and increasingly to the burden of chronic diseases in the United Kingdom, impacting both health and the economy. The introduction of fiscal measures that target unhealthy foods could provide a near-unique opportunity to shifting diets at scale for the benefit of both social and economic sustainability. This study estimates the expected health and economic benefits from the reduction in consumption of salt and sugar for four scenarios, each reflecting different manufacture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…This is similar to other research that has reported reductions in the prevalence of obesity as a result of drops in intakes of added sugars [29,30]. Modelling studies have shown both health and economic gains resulting from a reduced intake of added sugars [31][32][33][34], and as a result of the taxation of salt or foods high in salt [34][35][36][37][38]. Hence, the observed changes in overweight and obesity are likely to also generate improved health outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…This is similar to other research that has reported reductions in the prevalence of obesity as a result of drops in intakes of added sugars [29,30]. Modelling studies have shown both health and economic gains resulting from a reduced intake of added sugars [31][32][33][34], and as a result of the taxation of salt or foods high in salt [34][35][36][37][38]. Hence, the observed changes in overweight and obesity are likely to also generate improved health outcomes.…”
Section: Discussionsupporting
confidence: 84%